THE MAIN PROBLEMS IN ARCHITECTURAL MANAGEMENT OF SETTLEMENTS TERRITORIES - O. Drogitskaya (Управленческие науки)
The article considers the major management problems of settlements territories of different kinds in contemporary market conditions, defines the management structure of architectural activity at various designing stages. The structure of architectural activity is given, which exposes the major factors influencing the management tools of settlements territories development.The changes in demographic and planning structure, functional relationships in settlements development of different kinds are given. The stages and coherence of elaborating the designing papers for different designing objects are reproduced; the checklist of initial materials for designing is provided. The main architectural principles and requirements necessary for settlement functional and planning structure in its dynamic development accounting the changes in allocation the labour relationships, manufactures, housing development, transport system.The rural designing peculiarities are considered in details, the main functions of these settlements and its role of organizing the settlements territories are exposed.The necessity of working out the forecasting documents on perspective urban and rural development is substantiated regarding the architectural programmes defining the main directions of settlements development, the terms and objectives of architectural decisions’ implementation. The designing, planning and architectural decisions’ implementation tasks for the present moment and forecasting period are identified.The article states the issues of organizing the road network in urban and rural settlements planning structure dynamic development. The tasks and requirements in organizing the settlements transport system regarding the pedestrian traffic safety and reducing the population time costs in getting about the city. The peculiarities of organizing the road network in rural settlements regarding the needs of rural inhabitants are considered.On the basis of theoretical investigations, domestic and foreign practical experience the examples of formation the urban and rural settlements planning structure at various development stages are given.Scientifically proved suggestions on defining the perspective directions of social and economic settlements territories development on the basis of working out the complex designing and planning documentation taking into account the priorities of architectural policy regarding the public and commercial interests are introduced.